Rapid synthesis of Mn3O4 powder from pyro-synthesis of ethylene glycol-metal nitrate precursor assisted by nitric acid - Dias, Cristiane de Abreu; Nobre, Marcos Augusto de Lima [UNESP]; Lopes, Mauro C. (Carl Hanser Verlag, 2015)
The rapid synthesis of Mn3O4 powders by a two-step process of pyro-synthesis of ethylene glycol-metal nitrate precursor assisted by nitric acid is reported. A new strategy that accelerates the synthesis and allows obtaining highly pure crystalline Mn3O4 is discussed. The structural and morphological characteristics of the Mn3O4 powders are presented and discussed. The mechanism of formation of the Mn3O4 is also discussed. In comparison with other synthesis methods, the present method shows that the proposed route of synthesis has the main advantage of high production of the powder material in a very short time.
Keywords: Polyol; Nitric acid; Hausmannite